2012
DOI: 10.21608/eajbsz.2012.13513
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate Toxic Effect on Spleen Structure and Potentiality of Recovery in Adult Albino Rats

Abstract: Histological effects of Monosodium glutamate (MSG) commonly used as food additive on the spleen of adult Wistar rats were carefully studied. The rats (n=30), average weight of 115 gm were randomly assigned into four treatments (n=6) and control (n=6) groups. The rats in the treatment groups received 4 mg/kg IP of MSG for fourteen days, while the control group receives the same volume of distilled water intraperitoneally. The rats were sacrificed after the last day of injection (group 1) and on 14 (group 2), 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…The differentiation between red and the white pulps was distinct. Our results are consistent with those of [81]. They demonstrated that there were varying degrees of cellular recovery that improved with time after cessation of MSG treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The differentiation between red and the white pulps was distinct. Our results are consistent with those of [81]. They demonstrated that there were varying degrees of cellular recovery that improved with time after cessation of MSG treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Also the tubule came in contact with toxic chemicals during their excretion and elimination by the kidneys. Other mechanisms for the tubular lesions might involve reactive intermediates or oxidative stress, or both Alden and Frith, (1992) and Ebaid and Tag, (2012). These results agreed with Eweka (2007), Abass and Abd El-Haleem (2011), Eraque (2011), Afeefy et al (2012, Onaolapo et al (2013) and Dixit, et al (2014) who postulated that the degenerative effect of MSG on the cortex and medulla of kidney was due to the direct effect of toxins on cells of kidney which coincided with (Porter, 1994) who reported that one of the possible mechanism for the tubular lesions was the direct toxic effect on the cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The US FDA, the American Medical Association (AMA), the Joint FAO/WHO (1988) Expert Committee on Food Additives (JECFA), and the Scientific Committee for Food of the European Union (SCF, 1991) confirmed that the use of MSG is safe for the general population. Contrary to these findings, various studies have reported that MSG had toxic (Abass and Abd El-Haleem, 2011;AL-Mosaibih, 2013;Bojani c et al, 2009;Ebaid and Tag, 2012;Farombi and Onyema, 2006 etc. details were given in our publication) and genotoxic effects (Adeyemo and Farinmade, 2013;Farombi and Onyema, 2006;Ismail, 2012;Khatab and Elhaddad, 2015;Prasath et al, 2013;Renjana et al, 2013;Türko glu, 2015) in some test systems.…”
Section: Dear Editormentioning
confidence: 87%